Patient satisfaction with access, affordability and quality of diabetes care at Mohalla Clinics in Delhi, India - Sharma, Meenu Grover; Grover, Anu; Shekhawat, Kusum; Popli, Harvinder (Frontiers in Public Health, 2023)
Introduction: Mohalla Clinics have been set up to provide curative care for minor ailments free of cost within walking distance in the urban slums, thus making primary care more accessible and affordable. Studies evaluating patient satisfaction with treatment of chronic conditions, such as diabetes, in these clinics are lacking. Methods: A survey of 400 type 2 diabetes patients was conducted, split equally between Mohalla clinics (MC) and Private clinics (PC) in Delhi. Responses were analyzed using STATA17, applying appropriate statistical tests for the data type (Chi-square test, Mann-Whitney U test, Wilcoxon signed rank test, or two-sample t test). Results: Satisfaction level was high in both groups with no significant difference between mean satisfaction scores of MC patients and PC patients (Mean 3.79 vs. 3.85 respectively, p=0.4). However, MC patients reported a significant improvement in their satisfaction score after switching to MC (Mean 3.79 vs. 3.3 for the previous facility, p<0.05). Physician interaction with the patients was the most important factor in influencing the satisfaction score. Proximity to the clinic was the second most important factor for MC patients but was not as important for PC patients. Surprisingly, treatment success was considered an important factor for satisfaction level by <10% MC and <20% PC patients only, pointing to the need for patient education across both the groups. None of the MC patients mentioned free treatment as a contributory factor to high satisfaction, perhaps because most shifted from a government setup to MC. PC patients had more frequent follow-up visits and blood glucose monitoring, and longer consultation duration compared to MC patients, which were offset by access factors, thus not causing much difference to the satisfaction score between the two groups. Conclusion: MCs are making diabetes treatment accessible and affordable for the marginalized population of Delhi, despite not being designed or fully equipped to care for chronic diseases such as diabetes that require multi-specialty care to monitor and manage multiple co-morbidities and long-term complications. Positive perception of physician interaction and convenient location of the clinics are the two major contributors to the high satisfaction patients expressed with diabetes care at these clinics.